LGBTQIA+ Students Exhibit Differing Information Practices Based on Social Media Presence and Self-Identified Personality Type / de la Cruz, J., Winfrey, A., & Solomon, S. (2022). Navigating the network: An exploratory study of LGBTQIA+ information practices at two single-sex HBCUs. College & Research Libraries, 83(2), 278–295. https://doi.org/10.5860/crl.83.2.278 - Jasmin, Hilary (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective –To explore the information practices of LGBTQIA+ students and the potential for academic libraries to impact or influence these practices.Design – Focus groups and individual interviews.Setting – Two single-sex Historically Black Colleges and Universities (HBCUs) in the USA.Subjects – Twenty-three (23) LGBTQIA+ students who were recruited through convenience and snowball sampling.Methods – Students from the two colleges were hired and trained as recruiters and interviewers. Twenty-three (23) total interviews on information practices were conducted—nine (9) via focus group, fourteen (14) via individual interviews. No two students participated in both a focus group and an individual interview. Question banks were drafted by the authors for the interviewers to use.Main Results – Four primary themes arose in qualitative, applied thematic analysis: Acceptance, Support, Personality, and Social Media. Acceptance was further discussed by an interviewee stating one of the colleges in the study was started by lesbians, but this is silent in the campus history. Thus, it is difficult to feel accepted on a campus with so much erasure of LGBTQIA+ history. In conjunction with Acceptance is the lack of Support from both campuses, namely in events, activities, and other affirming programming for LGBTQIA+ students. Students felt the need for more explicit, unequivocal support for LGBTQIA+ students from campus administration. Findings also suggested that Personality, namely participants’ self-identified introversion, may contribute to information deprivation due to fewer social connections and therefore less information sharing. Social Media, the final theme, was noted as the most powerful forum for information sharing for students, as well as a space to normalize LGBTQIA+ movement and visibility. Finally, students viewed the library in a traditional light, such as a study space. The reasoning for some LGBTQIA+ students rejecting the library as a safe space was unclear, though the authors hypothesize this may be due to safety while returning back to their dorms at night.Conclusion – With a paucity of research in the information practices of LGBTQIA+ students, specifically those enrolled at HBCUs, the authors concluded that continued research is needed to understand how libraries can create safety and visibility. One primary mode for this might be to make more visible that libraries are not neutral, and that supporting LGBTQIA+ students should be a priority.